Francisella spp. in tilapias in Brazil: a review - Raghiante, Fernanda [UNESP]; Ferrasso, Marina de Mattos [UNESP]; Rodrigues, Marianna Vaz [UNESP]; Biondi, Germano Francisco [UNESP]; Martins, Otavio Augusto [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2017)
The growth of tilapicultura in the last three decades has done of this fish group one of the most extensive aquaculture of the world. The Nile tilapia (Oreochromis niloticus) is the most created specie in brazilian fish farms, because of its rusticity, fast growth, low water quality tolerance and considerable diseases resistance. However, an emergente bacteria, Francisella noatunensis orientalis, extremely virulent, has been responsible for tilapia deaths in brazilian farms. The molecular diagnosis like real time PCR (qPCR) has contributed to Francisella's species identification involved in granulomatous disease in these fishs. Prevention measures should be applied in order to reduce the Francisella contamination risk in fish farms, thus ensuring the squad health, avoiding losses to producers. This study aims to inform about the situation of francisellosis in tilapias in brazilian aquaculture.
Keywords: Francisellosis; tilapicultura; diagnosis